DISTILLER’S DRIED GRAINS SUPPLEMENTED Wz3ITH ENZYME COCKTAIL AND YEAST AFFECT EGG QUALITY, REPRODUCTIVE PERFORMANCE AND BLOOD PROFILE OF BREEDING HENS - Youssef A Attia; Rashed A. Alhotan; Fulvia Bovera; Nicola F. Addeoa; Reda A. Hassan; Adel D. Alqurash; Abd-El-Hamid E. Abd-El-Hamid; Wella S. Selim; Khalid A. Asiry (Journal of Animal and Plant Sciences, 2024)
This experiment aimed to examine the influences of distiller’s dried grains with solubles (DDGS) in breeding hen’s nutrition (0, 10, and 20%, respectively) with or without enzyme cocktail blend and yeast (Saccharomyces cerevisiae, SC) supplementation on the sustainability of quality of eggs and semen, fertility and hatchability, and blood biochemistry. In total, 360, twenty weeks old indigenous Inshas breeding hens and 36 Inshas cocks (for natural mating) were used in the experiment. Inshas is a crossing breed that originated from mating Sinai and White Plymouth Rock breeds. Hens and cooks of all experimental groups had approximately similar initial body weights (1,560 ± 12.3 g) at the start of the experiment and were divided into 12 groups, each containing three replicates (10 hens + 1 cock). Moreover, 60 cocks were divided into 12 groups of five cocks each and housed individually in cages for semen quality estimation using the artificial collection technique. Increasing DDGS up to 20% in diets of breeding hens decreased (p≤0.05) eggshell thickness compared to 0 and 10% DDGS, but it elevated (p≤0.05) color of yolk and Haugh unit score during the storage period. Dietary treatments did not significantly affect the percentage fertility, hatchability, and abnormality of embryos and body weight of day-old chicks. Semen quality was not significantly affected by dietary DDGS. Yeast supplementation increased (p≤0.05) sperm concentration per ejaculate by 5.21% and total normal sperm/ejaculate and sperm concentration by 5.87%. Increasing DDGS levels up to 10% and 20% decreased blood plasma total cholesterol by about 4.1%. Enzyme cocktail supplementation increased (p≤0.05) blood plasma Ca by 5.4% of 20% DDGS diets, but other blood plasma parameters were unaffected. Enzyme cocktail addition to DDGS diets also decreased plasma cholesterol by 3.63%. Feeding a 10% and 20% DDGS diet increased (p≤0.05) plasma creatinine by 9.75% and decreased the uric acid/creatinine ratio by about 11.1%. In conclusion, corn DDGS could be included in dual-purpose breeding hen’s diet up to 20% without adverse effects on the sustainability of the quality of eggs and semen, fertility and hatchability, and blood biochemistry. Furthermore, enzyme cocktail at 500 gm/ton feed and yeast at 1 kg/ton feed supplementations significantly and similarly improved eggshell thickness by 1.44-1.72%, and yeast increased sperm concentration and total sperm output per ejaculate.
Keywords: Distillers dried grains with soluble; breeding hens; multi-enzymes; Yeast; Fertility; Hatchability; Semen quality